Immunogenetics and genomics. - Hill, A (2001)
Immunogenetic analysis of disease susceptibility has been encouraged by the identification of strong HLA associations with several diseases of uncertain cause. Weaker HLA associations exist with a large number of infectious and non-infectious diseases and the mechanisms of these effects are beginning to be uncovered. Extensive analyses of non-HLA immunogenetic variants have also been undertaken and associations with a variety of genes identified. Genetic linkage analysis of multicase families has recently identified new major susceptibility loci for a few immunologically determined common diseases. However, the greatest potential for the future lies in genome-wide searches for susceptibility genes that individually might have quite modest effects but cumulatively have a large impact on individual risk. This new era of immunogenomics promises to provide key insights into disease pathogenesis and identify multiple molecular targets for intervention strategies.